Effective protection of West German industry - Ulrich Hiemenz; Kurt von Rabenau (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1973)
The establishment of the Common Market, a more inward looking trade policy on the part of the United States and, last but not least, the urgent demand of less developed countries for free access to the markets of the highly industrialized nations have revived international interest in the impact of foreign trade regulations on a country s domestic industry. One of the major points of interest is to analyse how trade regulations influence the comparative costs of domestic industries and consequently the structural pattern of industry. Protective measures such as tariffs, import quotas, subsidies and taxes alter a given industrial pattern by providing some industries with an advantage, while the economic conditions of others remain unchanged or even worsen. In the course of international trade liberalisation, reductions of trade barriers will create a need for adjustment processes in almost all economic activities. Effective rates of protection may help to achieve a better and smooth adjustment by providing information on the impact of trade regulations on gross production.
Keywords: 330